Cognitive Behavioral Therapy Assistance Model For Death Anxiety In The Elderly - Solihah, Ii; Ulty Desmarnita; Tarjuman, Tarjuman (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The elderly period is interpreted as a period of decline, especially in terms of physical and psychological functioning. One of the psychological problems in the elderly is anxiety about death. Family involvement in overcoming anxiety problems is very necessary. Cognitive behavioral therapy is an intervention to overcome anxiety about death in the elderly. The specific aim of this research is to reduce the anxiety level of the elderly so that they are able to face anxiety problems with a more positive mindset. The research method used a quasi-experimental (Pre-post test. Sampling was carried out using simple random sampling. The sample was selected as 89 respondents with the inclusion criteria being all elderly people who experienced anxiety about death. Data were analyzed using the Wilcoxon test and multiple logistic regression test. The results show that there is a relationship between place of residence (region) and a decrease in anxiety levels in the elderly (OR=0.77). This shows that elderly people living in Jakarta experienced a decrease in anxiety levels 7.7 times higher than elderly people living in Depok. Other results show that there is a relationship between age and a decrease in anxiety levels (OR=2.9), this shows that younger seniors (less than 68 years) experienced a decrease in anxiety levels 2.9 times faster than older seniors after receive cognitive behavioral intervention. The results of the study show that cognitive behavioral interventions in the form of relaxation therapy, reminiscence therapy, crossword puzzle therapy, counseling therapy, music therapy, and spiritual therapy can reduce anxiety about death in the elderly.